Effect of Gynotype, Age and Season on Reproductive Traits and External Egg Quality of Marshall and Arbor Acre Breeding Stocks - Aminami, M; Aliyu, J.; Babangida, S.; Mukaddas, J.; Mbursa, D.; Zanna, B.B.; Aminami, L. (Nigerian Journal of Animal Science, 2026)
The study was conducted at the Poultry Production Unit (PPU), Ministry of Agriculture and Animal Husbandry, Gombe, Gombe State, Nigeria to determine the effect of genotype age and season on fertility, hatchability, embryonic mortality and external egg quality on Marshall and Arbor acre broiler breeding stocks. A total of 2000 birds comprising 1000 each of Marshal and Arbor acre were used to obtain the data according to genotype, age and season. They were fed commercial diets and water was provided ad-libitum. Fertility, hatchability, early embryonic mortality (EEM) and late embryonic mortality (LEM) was calculated and presented in percentage. Egg external egg qualities were measured in g (weight), cm (length and width) and % (egg shape index), respectively. The data were subjected to analysis of variance (ANOVA) using General Linear Model while Duncan’s Multiple Range was used to separate their means. The overall means for fertility, hatchability, EEM, and LEM were 88.09, 82.60, 7.84 and 9.81 %, respectively. Effect of genotype was significant (P<0.05) on EEM and LEM but fertility and hatchability were not significant. Age and season were significant (P < 0.05) on all traits. The effect of genotype on egg weight (EW), egg length (EL), egg width (EWD) and egg shape index (ESI), were non-significant (P > 0.05), respectively. There was significant (P < 0.05) effect of age on egg weight, egg length, egg width and egg shape index. Egg weight was affected most by age 1 (26-34 weeks), followed by age 2 (35-43 weeks), while the least affected at age 3 (44-45 weeks) of age. There was significant (P < 0.05) effect of season on egg weight, egg length and weight but not on egg shape index. The study concluded that age and season had significant effects on fertility, hatchability and mortality as well as other traits, hence, there is need to adjust for these factors towards attaining optimal performance of these reproductive traits meanwhile, the best time for rearing broiler breeding stock in the study area is the dry cold season. Improving profit maximization, poultry breeders and farmers should give adequate management and required nutrition during the earlier stage of growth and also during dry hot and rainy season in order to improve the reproductive performance and avoid mortality in these broiler breeder stocks of chicken especially Arbor acre.